Transtympanic Visualization of Cochlear Implant Placement With Optical Coherence Tomography: A Pilot Study. Issue 8 (September 2022) - Wang, Junzhe; Chawdhary, Gaurav; Farrell, Joshua; Yang, Xiaojie; Farrell, Matthew; MacDougall, Dan; Trudel, Mathieu; Shoman, Nael; Morris, David P.; Adamson, Robert B. A.
Abstract : Objective: This study aimed to evaluate the ability of transtympanic middle ear optical coherence tomography (ME-OCT) to assess placement of cochlear implants (CIs) in situ. Patient: A 72-year-old man with bilateral progressive heredodegenerative sensorineural hearing loss due to work-related noise exposure received a CI with a slim modiolar electrode for his right ear 3 months before his scheduled checkup. Intervention: A custom-built swept source ME-OCT system ( λ o = 1550 nm, ∆ λ = 40 nm) designed for transtympanic middle ear imaging was used to capture a series of two- and three-dimensional images of the patient's CI in situ. Separately, transtympanic OCT two-dimensional video imaging and three-dimensional imaging were used to visualize insertion and removal of a CI with a slim modiolar electrode in a human cadaveric temporal bone through a posterior tympanotomy. Main Outcome Measure: Images and video were analyzed qualitatively to determine the visibility of implant features under ME-OCT imaging and quantitatively to determine insertion depth of the CI. Results: After implantation, the CI electrode could be readily visualized in the round window niche under transtympanic ME-OCT in both the patient and the temporal bone. In both cases, characteristic design features of the slim modiolar electrode allowed us to quantify the insertion depth from our images. Conclusions: ME-OCT could potentially be used in a clinic as a noninvasive, nonionizing means to confirm implant placement. This study shows that features of the CI electrode visible under ME-OCT can be used to quantify insertion depth in the postoperative ear.